2021
DOI: 10.1128/mra.00364-21
|View full text |Cite
|
Sign up to set email alerts
|

Near-Complete Genome Sequences of Five Siciniviruses from North America

Abstract: Here, we report near-complete genome sequences of sicinivirus from U.S. poultry flocks in 2003 to 2005 and Mexico in 2019. They show highest nucleotide identity (84.5 to 85.5%) with other members of the Sicinivirus genus. These sequences update knowledge on diversity and contribute to a better understanding of the molecular epidemiology of sicinivirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The present metagenomics study further confirmed the circulation of two recently discovered uncultivable intestinal poultry viruses in Belgium. Sicinivirus was discovered as a new picornavirus with unknown clinical manifestation of poultry in 2012 in Ireland [ 66 ] and currently has a worldwide documented distribution [ 67 70 ], while a retrospective metagenomic analysis showed its presence in samples dating back to 2003 [ 71 ]. Our study identified a significant normalized Sicinivirus read count in a pool of respiratory and intestinal tissue samples, suggesting a relatively high viral load.…”
Section: Discussionmentioning
confidence: 99%
“…The present metagenomics study further confirmed the circulation of two recently discovered uncultivable intestinal poultry viruses in Belgium. Sicinivirus was discovered as a new picornavirus with unknown clinical manifestation of poultry in 2012 in Ireland [ 66 ] and currently has a worldwide documented distribution [ 67 70 ], while a retrospective metagenomic analysis showed its presence in samples dating back to 2003 [ 71 ]. Our study identified a significant normalized Sicinivirus read count in a pool of respiratory and intestinal tissue samples, suggesting a relatively high viral load.…”
Section: Discussionmentioning
confidence: 99%
“…Goraichuk. Collaborators discovered five novel siciniviruses from poultry samples from North America [ 42 ]. In a different case, a 15-year-old sample confirmed the circulation of the GA08-like strain and complete genomes of avian coronavirus 4 years before its first reported outbreak [ 43 ].…”
Section: Short-read Sequencing On Poultry and Avian Speciesmentioning
confidence: 99%
“…In recent years, untargeted next-generation sequencing (NGS) technology has been increasingly employed for the detection and characterization of RNA viruses, particularly in the context of avian diseases ( Chen et al, 2013 ; Tang et al, 2015 ; Goraichuk et al, 2016 , 2017 , 2019 , 2021a , b ; Croville et al, 2018 ; Ferreri et al, 2019 ; Tal et al, 2019 ; Patzina-Mehling et al, 2020 ; Crossley et al, 2021 ; Chrzastek et al, 2022 ; Damir et al, 2023 ; Ip et al, 2023 ; Kariithi et al, 2023 ; Techera et al, 2023 ). Avian viruses, including highly pathogenic avian influenza virus (AIV) and Newcastle disease virus (NDV), pose significant threats to poultry populations and public health ( Alexander, 1998 ; Suarez, 2017 ; Swayne et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%